On the Reactivity of NHCtBuAuCl towards Rb6Cs6Si17: The First Gold‐Silicon Cluster [(NHCtBuAu)6(η2‐Si4)]Cl2·7NH3 and an Imide Capped Gold Triangle (NHCtBuAu)3NHCl. Issue 18 (30th September 2020) - Tiefenthaler, Susanne M.; Streitferdt, Verena; Baumann, Josef; Gaertner, Stefanie; Gschwind, Ruth M.; Korber, Nikolaus
Abstract : Crystals of the two new compounds (NHC t Bu Au)3 NHCl and [(NHC t Bu Au)6 (η 2 ‐Si4 )]Cl2 · 7NH3 could be isolated from the reaction of Rb6 Cs6 Si17 with NHC t Bu AuCl in the presence of [2.2.2]‐cryptand in liquid ammonia. Both compounds were characterized by single‐crystal X‐ray diffraction and crystallize trigonally without any alkali metals or chelating ligands. Additionally, the crystal of [(NHC t Bu Au)6 (η 2 ‐Si4 )]Cl2 · 7NH3 was further interpreted by means of ELF and NBO calculations. In the case of (NHC t Bu Au)3 NHCl, NMR experiments provided an exceptional insight into the reaction processes in solution and allowed for the detection of sequential precursors. In the class of capped gold triangles (NHC t Bu Au)3 NHCl impresses with its unique characteristics of being capped by an imide and bound to N ‐heterocyclic carbenes as ligands instead of the ubiquitously employed phosphines. The gold capped silicon tetrahedron [(NHC t Bu Au)6 (η 2 ‐Si4 )]Cl2 · 7NH3 represents the first known silicide‐gold compound, as well as the first known functionalized Zintl anion, crystallized with a cationic central moiety. Abstract :